PROBABILITY INTERPRETATION OF FINITE DIFFERENCE AND FINITE ELEMENTS’ APPROXIMATIONS IN INITIAL VALUE BOUNDARY PROBLEMS OF ELLIPTIC TYPE - Сеничак, Василь Михайлович; Сеничак, Владислав Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
We consider the probability interpretation of finite-element approximations of the finite elements method (FEM). The connection between a finite element and transition probabilities in the scheme of random walks is being considered. A fundamentally new version of the Monte Carlo method – the method of accelerated statistical tests is proposed.